2018
DOI: 10.1111/1460-6984.12423
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and emotion regulation strategies in children with and without developmental language disorder: a longitudinal study

Abstract: BackgroundDepressive symptoms are common in children with developmental language disorder (DLD). However, risk and protective factors contributing to these problems are currently underspecified.AimsThe current longitudinal study examined the role of emotion‐regulation (ER) strategies in the severity of depressive symptoms in children with and without DLD, taking into account the severity of communication problems of children with DLD.Methods & ProceduresWe followed clinically referred children with DLD (n = 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 48 publications
2
41
1
2
Order By: Relevance
“…Instead, the communication problems may cause an inability to effectively differentiate and communicate emotions, which in turn puts children at risk for internalizing problems. As in previous studies, we found mixed results between the severity of communication problems in children with DLD and their internalizing problems (St Clair et al 2010;Van Daal et al 2007).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Instead, the communication problems may cause an inability to effectively differentiate and communicate emotions, which in turn puts children at risk for internalizing problems. As in previous studies, we found mixed results between the severity of communication problems in children with DLD and their internalizing problems (St Clair et al 2010;Van Daal et al 2007).…”
Section: Discussionsupporting
confidence: 72%
“…Only pragmatic problems, such as the initiation of conversations, non-verbal communication, use of context, and stereotypical language use, represented a risk factor for higher levels of internalizing problems (St Clair et al 2010). Similarly, the level of somatic complaints of 5-year-olds with DLD were unrelated to their phonological, semantic, and syntactic language problems, whereas social anxiety was related to more phonological and semantic language problems (van Daal et al 2007). Adolescents with DLD also reported more social anxiety when they had more expressive language problems, but this relation was fully mediated by their social skills (Wadman et al 2011).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, early language difficulties are known to be a good predictor of emotional problems in late childhood and adolescence [16]. In this vein, and since emotional problems seem to increase from childhood to adolescence, anxious and depressive traits are common among teenagers with this disorder [16,18]. Therefore, adolescents with DLD are more vulnerable to emotional disturbances than their typical peers [19] and report higher indexes of internalized and externalized emotional difficulties, more (and more severe) emotional symptoms, and poorer psychological functioning than typical children and adolescents [11,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Norbury a Sonuga-Barke v roce 2017 přicházejí s důkazy, že na psychiatrických klinikách má celá jedna třetina nediagnostikovanou jazykovou poruchu, 40 % mladých delikventů vykazuje jazykové deficity, z toho čtvrtina splňuje kritéria jazykové poruchy a dívky s touto diagnózou jsou více ohroženy sexuálním zneužíváním. Nizozemsko-britská víceúrovňová analýza potvrdila vyšší úroveň depresivních symptomů u mladých lidí s jazykovou poruchou ve srovnání s intaktními vrstevníky (Bedem et al, 2018).…”
Section: K Důsledkůmunclassified